Alternatives for Telco Data Network: The Value of Spatial and Referral Networks for Churn Detection. Issue 3 (3rd July 2021) - Colot, Christian; Baecke, Philippe; Linden, Isabelle
ABSTRACT: The value of communication network has received significant attention in the literature on churn prediction, while little is known about the potential business value of alternative networks. This knowledge would help telephone companies to make timely strategic decisions in our evolving economic environment where traditional communication technologies are declining. This study assesses to which extent two alternative networks might (1) structurally substitute this network and (2) complement this network for churn prediction within telephone companies.